Variation of seed zinc in a local upland rice germplasm from Thailand - Jaksomsak,P. (Cambridge University Press, 2015)
This study examined variation in seed zinc (Zn) in a local upland rice germplasm that may affect adaptation in a system of slash-and-burn. Individual seed Zn in farmers' seed lots of local upland rice varieties from a slash-and-burn system was evaluated by staining with dithizone (DTZ). Concentration of Zn in the farmers' seed lots and their single-seed descent genotypes grown at Chiang Mai University was determined by chemical analysis. The DTZ staining of individual seeds in most of the farmers' seed lots covered the intensity of standards that ranged from 19 mg Zn/kg (RD21) to 31 (Nam Roo) mg Zn/kg. Zinc content by chemical analysis was closely correlated with the weighted-average staining for each seed lot. Almost all of the single-seed descent genotypes had higher seed Zn than RD21; two-thirds were higher than Nam Roo. The variation within seed lots detected by DTZ staining was confirmed by seed Zn in the single-seed descent genotypes. Evolutionary adaptation to soil with limited Zn, exacerbated by alkalinity of the ash from slash-and-burn, is made possible by variation in seed Zn among individuals growing together in the same field, and benefits the eaters with Zn-enriched seed. Copyright © NIAB 2014.